THE EFFECT OF EDUCATIONAL VIDEOS ON KNOWLEDGE ABOUT MENOPAUSE OF ELDERLY POSYANDU PARTICIPANTS IN BLABAK VILLAGE, KEDIRI REGENCY - Priyanto, Kurniawan Edi; Saifulah, Dedi (Master of Public Health Program Universitas STRADA Indonesia, 2025)
One of the factors that affect women's readiness in facing menopause is maternal knowledge. The cause of the lack of maternal knowledge is education where each mother has a different last education. This study aims to analyze the effect of health education on knowledge about menopause in elderly posyandu participants in Blabak Village, Kediri Regency. The research design used by the researcher is a pre-experimental design with one-group pre-post test design research. The number of samples is 36 respondents with a population of 40 elderly people. with a simple random sampling technique. The research instrument uses a questionnaire. The independent variable is health education. The dependent variable is knowledge about menopause. The results of knowledge about menopause before health education were in the poor category of 27 respondents (75%). After health education about menopause, respondents experienced an increase in the category to good by 33 respondents (91.7%). The results of the study using the Wilcoxon Test with a value of α = 0.05 obtained a significant result of 0.000, because the significant value <0.05 which means that there is an effect of health education on knowledge about menopause in elderly posyandu participants in Blabak Village, Kediri Regency. In this study, knowledge after being given health education about menopause has increased. This proves that health education can be obtained, one of which is from listening and reading on health education videos. very influential on a person's knowledge because they get health education with material that is given repeatedly and discussions are held with respondents.